Psychological correlates of training load among athletes - Terry, P. C.; Galambos, S. A.; West, J.; Iizuka, C. A. (42nd Australian Psychological Society Annual Conference 2007, 25-29 Sept 2007, Brisbane, Australia, 2007)
Excessive training loads have been identified as a risk factor for injury among athletes, although psychological monitoring may help to ameliorate this risk. As part of an investigation of injury prevention, the present study assessed relationships between perceived stress and recovery, mood responses, and physical training load for 60 athletes (male = 31, female = 29) from basketball, golf, hockey, and rowing over a period of up to 16 weeks. Training duration and ratings of perceived exertion (RPE) were recorded daily while the Brunel Mood Scale, the Perceived Stress Scale, and the Recovery-Stress Questionnaire for Athletes (RESTQ) were completed weekly. Training load was calculated as training duration x RPE. Collectively, psychological indices predicted 24.3% of training load variance. Best predictors were RESTQ scores for physical complaints, success, social recovery, physical recovery, emotional exhaustion, and self-efficacy. Younger athletes reported more positive mood responses, less perceived stress and more positive RESTQ scores. Females reported higher training loads, more positive RESTQ scores, and more positive mood responses. Type of sport differences were identified for almost all psychological indices. Results showed that psychological indices are reflective of training load and may play an important role in injury prevention.